Researching health needs a community-based approach - Payne, Judy.; Sage eBooks (London : SAGE, 1999)
Social Evidence and Health Needs is a practical, easy to use introduction to the main social research techniques used to gather evidence about the health needs of local communities.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health surveys; Health planning; Medical care -- Needs assessment; Electronic books